Peningkatan Kemampuan Pemahaman Konsep Penyajian Data Menggunakan Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) di Kelas IV SDN 01 Bandar Buat Kota Padang - Asnah Aisyah; Mursal Dalais (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to determine the increase in students' ability to understand concepts in the data presentation material in Grade IV Elementary School using the Indonesian Realistic Mathematics Education (PMRI) approach. This study uses a qualitative and quantitative approach. The type of research used is classroom action research conducted in two cycles. The results of this study indicate that first, there is an increase in the implementation of the learning process using the PMRI approach from the aspects of teachers and students. The implementation of the learning process using the PMRI approach from the aspect of the teacher has increased from 72.5% to 90% this indicates an increase from the first cycle of 17.5%. From the aspect of students the implementation of the learning process using the PMRI approach has increased from 72.5% to 85% this indicates an increase of 12.5%. The increase was also seen from the results of the concept understanding tests of students using the PMRI approach, namely in the first cycle the average students gained was 71.67 with sufficient qualifications and increased in cycle 2 to 86.25 with excellent qualifications. Therefore, it can be concluded that the PMRI approach can improve the ability to understand the concept of presenting data of students in class IVA SDN 01 Bandar Untuk Kota Padang.